A Survey on Operations Research Applications in Construction Management - Yazgaç, Tülin; Özdamar, Linet (İstanbul Kültür Üniversitesi Yayınları, 2002)
In today’s competitive world, construction companies should integrate the expertise of multiple disciplines to remain in the business. Interdisciplinary aplication areas in construction management involve concepts such as total quality management , risk management, human factors, resource manageement cash flow management, and knowledge-based systems for resolving issues such as developing the activity network topology and resource allocation . Our aim is to summarize the related research and the applied contributions to construction projects from different fields and to indicate possible future areas of interdisciplinary appications.

Günümüzün rekabet ortamında, inşaat firmalarının, farklı disiplinlerin uzmanlıklarını bünyelerinde bütünleştirmeleri kaçınılmaz olmuştur. Yapım yönetiminde disiplinlerarası uygulama alanları; toplam kalite yönetimi, risk yönetimi, insan faktörleri, kaynak yönetimi, nakit akışı yönetimi ve bilgiye dayalı sistemler gibi kavramları içermektedir. Amacımız, bu konudaki ilgili araştırmaları ve farklı alanlardan inşaat projelerine yapılan katkıları özetlemek ve disiplinlerarası uygulamaların gelecekteki olası kullanım alanlarını belirtmektedir.
Keywords: construction management; inşaat yönetimi; operations research techniques; yöneylem araştırma teknikleri; soft computing methods; yumuşak hesaplama yöntemleri